Pengaruh Nisbah Polypropylene / Serat Pelepah Sawit Dan Kadar Maleated Polypropylene (MAPP) Terhadap Sifat Dan Morfologi Wood Plastic Composites (WPC) - Nurul Aini Thaibil Fadhly; Irdoni HS; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of the materials that can be used as a component in the manufacture of Wood Plastic Composite (WPC) is a palm frond fibers. Palm frond is one of the solid waste of oil palmplantations and abundant availability has not been utilized optimally. The purpose of this study was to determine the influence of the ratio of polypropylene (PP) / palm frond fibers and Maleated polypropylene compatibilizer levels of the properties and morphology of WPC. WPC samplesprepared by the method of melt blending between palm frond fibers, PP, Maleated polypropylene (MAPP), and paraffin for 15 minutes at a temperature of 170 ° C and a rotor speed of 80 rpm using Internal Mixer. The size of the palm frond fibers used is 1 cm. While the ratio of the weight of PP/palm frond fibers is 50/50, 60/40 and 70/30 and the addition of MAPP of 0%, 4% and 5%. Testing experiments were prepared to mechanical testing consist of tensile and flexural strength and physical testing consist of density, water absorption, and swelling thickness. Scanning Electron Microscopy was used as a morphology testing. The results showed that the best mechanical properties in a ratio of polypropylene / palm frond fibers (60/40), MAPP (5%), with the value of tensile strength 256.05 kgf/cm2 and flexural strength 598 kgf /cm2.The best physical properties of water absorption at a ratio (60/40) with MAPP (0%) is 0,97%, the density at a ratio (60/40) and MAPP (5%) is 1,07% and swelling thickness at a ratio (50/50) with MAPP (0%) is 0,17%.Keywords: maleated polypropylene, morphology, palm frond fibers, mechanical properties , wood plastic composite